Application of LKPD Social Studies Based Collaborative Learning Model Structured Problem Solving Type in Improving the Completeness of Class VII Students' Learning Outcomes at SMP Negeri 1 Tenggarong Seberang - Dorkas Ria Marcelina Nainggolan; Sudarman Sudarman; Nasib Subagio (Educational Studies: Conference Series, 2022)
Application of Social Worksheets Based on Collaborative Learning Model Structured Problem Solving Type in Improving Mastery of Student Learning Outcomes aims to determine the completeness of class VII A students' learning outcomes at Tenggarong Seberang 1 Public Middle School by implementing Social Worksheets based on the Collaborative Learning Model Structured Problem Solving Type and knowing how to apply Social Worksheets based on the Collaborative Learning Model of the Structured Problem Solving Type in improving the completeness of class VII A students' learning outcomes at SMP Negeri 1 Tenggarong Seberang. This type of research is classroom action research (PTK) which is carried out in two cycles with research flows namely planning, implementing, observing, and reflecting. The subjects of this study were 32 students in class VII A of SMP Negeri 1 Tenggarong Seberang. The technique of collecting data in this study uses observation sheets, learning achievement tests and documentation. Research data analysis techniques using qualitative and quantitative descriptive analysis techniques. The indicator of success is 75% of the number of students reaching the specified KKM, which is ≥ 75. The results showed that there was an increase in the completeness of student learning outcomes with the implementation of the IPS LKPD based on the Collaborative Learning Type Structured Problem Solving model in each cycle, in cycle I the average value of student learning outcomes was 70 (59.3%) while in cycle II it was obtained the average value of student learning outcomes is equal to 82.3 (81.25%). From the results of the research that has been done, it can be concluded that by using social studies worksheets based on collaborative learning models of the structured problem solving type, it can improve the completeness of student learning outcomes. This can be seen from the difference in the increase in mastery learning outcomes (cycle I to cycle II of 21.95%).